Canvassing KUR Products At Sharia Pegadaian UPS RS. Suwondo Pati - Soeparwi; Rizqi Ardika Akbar; Fikrotul Munawaroh (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Canvassing activities for KUR products at the Sharia pawnshop UPS RS. Suwondo Pati was carried out by Internship Students from the IAIN Kudus Sharia Banking study program, which is a Field Experience Practice activity for customers that focuses on canvassing KUR products in the Pati unit sharia pawnshops. This activity was divided into 3 stages, namely the first stage in the form of supervision of KUR products, the second stage in the form of implementation and the third stage in the form of supervision carried out by students in marketing KUR products around the Pati area. With this activity, it is hoped that customers can understand KUR products at the UPS RS sharia pawn shop. Suwondo Pati and Through this canvassing activity, Pegadaian Syariah seeks to provide an in-depth explanation of the benefits and process of applying for KUR to prospective borrowers. In addition, by interacting directly, the sales and marketing of Pegadaian Syariah can better understand the needs and challenges faced by Micro, Small and Medium Enterprises, so that they can provide more targeted financial solutions.